Utilization of online discussions to enhance students' engagement with William Golding's "Lord of The Flies" - Farhan, Raed Nafea (2021)
In the current educational landscape, we cannot deny the significant influence and effectiveness of technology implementation in education. However, the teaching of literature components in EFL classes in Iraq is most often still adopting traditional approaches of "tell them and test them". To improve the quality of English literature teaching and learning as well as to fulfill the needs of current students, shifting from the traditional to technology-enhanced approach is rapidly becoming a necessity. Thus, this one group pretest-posttest quasi-experimental study was aimed at investigating the impact of technology integration in the EFL literature classroom, specifically examining the impact of collaborative online discussions (ODF) via Facebook Messenger on students’ engagement with the literary text through examining their test performance, journal responses and attitudes. In the study, 45 undergraduate students from the English department/College of Education of a University of Al-Anbar in Iraq conducted online discussions with group members on various elements of the literary text. The main data collection instruments were tests and journal entries which were aimed at measuring and investigating the effects of the online discussions on students’ performance and responses; the pre-test and pre-journal entry were administered prior to the online discussions and the post-test and post-journal entry were done after the intervention. Survey questionnaires to gauge students’ attitude were also distributed at the end of the study. Findings showed that the students were positive about the implementation of online discussions in their literature classroom and would recommend it as an interesting teaching approach as shown by their "attitudes towards the integration of ODF (Overall Mean = 4.03, SD = 0.84)" and "perceptions on the effects of ODF on learning the novel (Overall Mean = 3.99, SD = 0.87)". In addition, paired samples t-test analysis indicated that the online discussions had statistically significant impact on students’ test performance t (44) = 8.28, p <.001(two-tailed), and responses in their journal entries, t (44) = 8.96, p <.001(two-tailed). For students' performance level, comprehension level recorded the highest mean improvement, m = 20.86, whereas analysis level recorded the lowest, m = 6.62 (total marks is 400 marks). In terms of student's response levels, comprehension also recorded the highest mean improvement, m = 1.13, whereas evaluation level recorded the lowest, m = 0.49 (total marks is 16 marks). A Pearson correlation coefficient also examined the relationship between performance and response, and it showed a moderate positive correlation (r = 0.456, p<.002). In conclusion, the study revealed that the contribution of online discussion in engaging students with the literary text was beneficial and should be recommended for the literature classroom.